Female Babies and Risk-Aversion - Ganna Pogrebna; Andrew J. Oswald; David Haig (Institute of Labor Economics (IZA), 2017)
Being told the sex of your unborn child is a major exogenous 'shock'. In the first study of its kind, we collect before-and-after data from hospital wards. We test for the causal effects of learning child gender upon people's degree of risk-aversion. Using a standard Holt-Laury criterion, the parents of daughters, whether unborn or recently born, are shown to be almost twice as risk-averse as parents of sons. The study demonstrates this in longitudinal ('switching') data and cross-sectional data. The study finds it for fathers and mothers, babies in the womb and recently born children, and for a West European nation and an East European nation.
Keywords: J16; C93; C90; D81; 330; pregnancy; risk attitudes; daughters; child gender; Trivers-Willard hypothesis